2006
DOI: 10.1557/jmr.2006.0317
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of silicon carbide and the formation of silica polymorphs

Abstract: The oxidation of both single crystal and relatively pure polycrystalline silicon carbide, between 973 and 2053 K, resulted in the formation of cristobalite, quartz, or tridymite, which are the stable crystalline polymorphs of silica (SiO 2 ) at ambient pressure. The oxide scales were found to be pure SiO 2 with no contamination resulting from the oxidizing environment. The only variable affecting the occurrence of a specific polymorph was the oxidation temperature. Cristobalite was formed at temperatures ജ1673… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 42 publications
2
16
1
Order By: Relevance
“…During SiC oxidation SiO 2 crystallization starts between 700 and 1400°C . The wide range in temperature is due to the extreme sensitivity of silica crystallization to impurities, and to H 2 O and other gases in the oxidizing environment .…”
Section: Introductionmentioning
confidence: 99%
“…During SiC oxidation SiO 2 crystallization starts between 700 and 1400°C . The wide range in temperature is due to the extreme sensitivity of silica crystallization to impurities, and to H 2 O and other gases in the oxidizing environment .…”
Section: Introductionmentioning
confidence: 99%
“…). The high‐temperature passive oxidation of silicon carbide is known to proceed via formation of amorphous silica which crystallizes to different polymorphs of silica (cristobalite, tridymite, and quartz) at higher temperatures and longer treatment time . It has also been reported that the reduction of fayalite in H 2 at temperatures below 1100°C yields metallic Fe co‐existing with amorphous silica .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that crystalline phases of SiO 2 such as quartz, tridymite, and cristobalite on SiC substrate is produced by the oxidation of SiC substrate at temperatures higher than 700°C [27]. At temperatures above 1200°C, the initially amorphous SiO 2 crystallizes, beginning at the oxideatmosphere interface, and then b-cristobalite crystals appear [28].…”
Section: Synthesis and Microstructural Observation Of Single-crystallmentioning
confidence: 99%
“…The structure of SiO 2 nanotube begins to show amorphization after as little as 20 s irradiation, is mostly amorphous after 1 min, and appears completely amorphous after 4 min under these beam irradiation conditions. Quartz and silica glass are stable, whereas a-cristobalite is unstable, at room temperature [27]. It is therefore relatively easy to amorphize cristobalite nanotubes by electron beam irradiation.…”
Section: Amorphization Of Sio 2 Nanotubes By Electron Beam Irradiationmentioning
confidence: 99%